(x-2)(x+2)+6=(2x-3)²-3x(x-1)
Răspunsuri la întrebare
Răspuns de
2
(x-2)(x+2)+6=(2x-3)²-3x(x-1)
x²-4+6=4x²-12x+9-3x²+3x
x²+2=x²-9x+9
x²-x²+9x=9-2
9x=7
x=7/9
x²-4+6=4x²-12x+9-3x²+3x
x²+2=x²-9x+9
x²-x²+9x=9-2
9x=7
x=7/9
Răspuns de
2
(x - 2)(x + 2) + 6 =(2x - 3)² - 3x(x - 1)
x² - 4 + 6 = 4x² - 12x + 9 - 3x² + 3x
x² + 2 = x² - 9x + 9
9x = 9 - 2
x = 7/9
x² - 4 + 6 = 4x² - 12x + 9 - 3x² + 3x
x² + 2 = x² - 9x + 9
9x = 9 - 2
x = 7/9
Alte întrebări interesante
Limba română,
8 ani în urmă
Limba română,
8 ani în urmă
Geografie,
8 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă